Coupled thermo-hydro-mechanical modeling on well pairs in heterogeneous porous geothermal reservoirs. (15th March 2019) - Liu, Guihong; Pu, Hai; Zhao, Zhihong; Liu, Yanguang
Abstract: Production water reinjection plays an important role in geothermal reservoir management. Heterogeneous porous geothermal reservoir models considering the spatial distributions of permeability and rock heat capacity are generated. In total, 200 realizations with different permeability fields were considered. A fully coupled modeling of reservoir deformation, fluid flow, and heat transport was performed on each realization using the finite element method. The results showed that heterogeneity induced channeling appears in the geothermal reservoirs with increasing heterogeneity of permeability, through which the injected production can quickly reach the production well. This causes the shorter thermal breakthrough time at production wells, and the lower reservoir surface settlement. In geothermal reservoir models considering the correlation between heat capacity and permeability, the thermal breakthrough curves and the reservoir surface settlement were the same as the reservoir models of the constant heat capacity. With increasing correlation length, the possibility of flow channels appearing in well pair system increases, causing a short average thermal breakthrough time and a lower surface settlement around the injection well. The existence of preferential flow channels between injection and production wells indicates that an equivalent flow channel model can be approximately simulate geothermal doublets in heterogeneous reservoirs. Highlights: Heterogeneity induced channeling appears in geothermal reservoirs. The short thermal breakthrough time occurs in heterogeneous geothermal reservoirs. The low surface settlement occurs in heterogeneous geothermal reservoirs. The existence of preferential flow channels verifies the equivalent channel models.